Pengendalian Pembangunan Pada Kawasan Konservasi di Kampung Akuarium Jakarta - Rezka Ajeng Larasati; Vivaldi Rizqi Hisyam; Dedi Hantono; Jundi Jundullah Afgani (REKA RUANG, 2021)
Kampung Akuarium is an urban village located in Jakarta. It is located in the red zone according to the municipal regulation on the detailed spatial plan. Based on the regulation, Kampung Akuarium is delineated as the area intended for the local government needs. This research was conducted to investigate the utilization of the municipal regulation on land use control in Kampung Akuarium. This research also aims to reveal the role of municipal regulation to solve the problem in the Kampung Akuarium. This research utilizes the descriptive-qualitative method. The data was collected through an extensive literature review. The result shows that the development control is not well applied in the development of Kampung Akuarium. The land-use control mechanism still caused several conflicts which burden the urban village dwellers.